A new species of Phyllurus leaf-tailed gecko (Lacertilia: Carphodactylidae) from Scawfell Island, mid-east Queensland, Australia - Hoskin, Conrad J. (Zootaxa, 2023)
A recent targeted reptile survey of Scawfell Island, in the South Cumberland Group, revealed a species of Phyllurus gecko that could not be morphologically assigned to any described species. Here I describe this as a new species, Phyllurus fimbriatus sp. nov., based on differences in a number of morphometric and scalation traits from congeners. Phyllurus fimbriatus sp. nov. is restricted to deeply-piled boulder habitat under rainforest canopy on Scawfell Island, approximately 50 km offshore from Mackay in mid-east Queensland. A survey in rocky, rainforest habitat on nearby Carlisle Island failed to find the species, and other nearby islands appear to lack sufficiently deep rock outcropping to support the species. Phyllurus fimbriatus sp. nov. is known from two small patches of habitat on Scawfell Island, but it is common within these, and is likely to be found in other suitable habitat patches on the island. Based on assessment of imagery, the total area of habitat occupied may be < 1 km2. The island is protected within South Cumberland National Park, but fire encroachment from adjacent dry sclerophyll habitats, climate change, competition from introduced Asian House Geckos (Hemidactylus frenatus Duméril & Bibron, 1836), and poaching are potential threats.